Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s10162-016-0614-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulse Polarity on Thresholds and on Non-monotonic Loudness Growth in Cochlear Implant Users

Abstract: Most cochlear implants (CIs) activate their electrodes non-simultaneously in order to eliminate electrical field interactions. However, the membrane of auditory nerve fibers needs time to return to its resting state, causing the probability of firing to a pulse to be affected by previous pulses. Here, we provide new evidence on the effect of pulse polarity and current level on these interactions. In experiment 1, detection thresholds and most comfortable levels (MCLs) were measured in CI users for 100-Hz pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 29 publications
13
54
0
Order By: Relevance
“…A previous study had shown that, as for the TP-A and TP-C pulse trains used here and for pseudomonophasic pulse trains, the loudness of supra-threshold QP-A pulse trains was consistently greater than that of QP-C pulse trains at the same current (Carlyon et al, 2013). Macherey et al (2017) found that, across subjects, the difference between QP-A and QP-C thresholds correlated strongly with that between SYM-A and SYM-C thresholds, demonstrating that the idiosyncratic differences observed across subjects were not simply due to measurement noise.…”
Section: Comparison To Previous Studiesmentioning
confidence: 53%
See 1 more Smart Citation
“…A previous study had shown that, as for the TP-A and TP-C pulse trains used here and for pseudomonophasic pulse trains, the loudness of supra-threshold QP-A pulse trains was consistently greater than that of QP-C pulse trains at the same current (Carlyon et al, 2013). Macherey et al (2017) found that, across subjects, the difference between QP-A and QP-C thresholds correlated strongly with that between SYM-A and SYM-C thresholds, demonstrating that the idiosyncratic differences observed across subjects were not simply due to measurement noise.…”
Section: Comparison To Previous Studiesmentioning
confidence: 53%
“…More recently, two studies have shown that, although detection thresholds do not 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 differ overall between stimuli of opposite polarity, individual CI listeners show idiosyncratic but consistent polarity effects. Macherey et al (2017) measured thresholds for trains of symmetric biphasic pulses with either anodic or cathodic leading polarity ("SYM-A" and "SYM-C"), as well as for trains of so-called quadraphasic ("QP") pulses. The QP pulses were constructed by abutting two SYM pulses of opposite leading polarity, such that the central portion consisted of two anodic (QP-A) or cathodic (QP-C) phases.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
“…These include signal detection in quiet and supra-threshold measures. Authors have investigated the variation in not only the absolute level of thresholds (Pfingst and Xu 2004 ; Bierer et al 2015 ) but also how they are influenced by pulse rate (“multi-pulse integration, MPI”; Zhou and Pfingst 2014 ; Zhou et al 2015 ; Zhou and Pfingst 2016 ), pulse polarity (Macherey et al 2017 ), and stimulation mode (Bierer 2007 ; Bierer and Faulkner 2010 ). Supra-threshold tasks have included modulation detection (Garadat et al 2012 ; Garadat et al 2013 ), gap detection (Bierer et al 2015 ), and rate discrimination both at low and high rates (Cosentino et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulus polarity can affect not only MCLs but also thresholds. Unlike MCL measures, the direction of the polarity sensitivity at threshold varies consistently across listeners and electrodes, and some electrode-listener combinations reveal lower thresholds for cathodic than for anodic stimulation (Macherey et al 2017 ; Mesnildrey et al 2017 ). These combinations may reflect local regions of good neural survival in which a relatively high proportion of peripheral processes remain.…”
Section: Introductionmentioning
confidence: 99%
“…One could therefore speculate that the neuronal membrane is excited by the first anodic phase in rampDOWN-A and by the second phase in Rec-A, Rec-C and rampDOWN-C. In addition, action potentials evoked by rampDOWN-A could be less influenced by the phenomenon of 'anodal blocking' [30][31][32] . Here, the stimulus elicits an action potential near the terminal of the nerve fiber, but the stimulus itself prevents its propagation due to a strong hyperpolarization of the more distant and central part of the fiber.…”
Section: Ramped Shapes Have Steeper Eabr Growth Function Slopes Compamentioning
confidence: 99%